2023
DOI: 10.3389/fmicb.2023.1117905
|View full text |Cite
|
Sign up to set email alerts
|

Enteric nervous system damage caused by abnormal intestinal butyrate metabolism may lead to functional constipation

Abstract: Functional constipation (FC) is a high morbidity gastrointestinal disease for which dysfunction in the enteric nervous system is a major pathogenesis mechanism. To enhance our understanding of the involvement of intestinal microbiota and its metabolites in the pathogenesis of FC, we conducted a shotgun metagenomic sequencing analysis of gut microbiota and serum short-chain fatty acids (SCFAs) analysis in 460 Chinese women with different defecation frequencies. We observed that the abundance ofFusobacterium_var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…In our MR results, some SCFA-producing bacteria, such as Peptococcus ( Wang H. et al, 2023 ), Ruminococcus2 ( Wu et al, 2023 ), Clostridiaceae1 ( Vojinovic et al, 2019 ), and Ruminococcaceae ( D'Amato et al, 2020 ; Zhou et al, 2022 ) were identified to be protective to HSCR, some of which in HSCR was significantly decreased, and were correlated with SCFAs. Animal studies suggested that SCFAs could independently stimulate the enteric neural stem cell phenotype, thereby improving enteric neural disorders ( Fung et al, 2021 ; Tian et al, 2023 ; Wang L. et al, 2023 ). Recent studies revealed that SCFA promoted enterochromaffin cells (ECs) to secrete 5-hydroxytryptamine (5-HT; Atarashi et al, 2013 ; Furusawa et al, 2013 ; Reigstad et al, 2015 ; Yano et al, 2015 ), which is regulated by the calcitonin selective reuptake transporter (SERT) of epithelial cells and plays crucial roles in enteric neuroregeneration and neuroprotection ( Bian et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our MR results, some SCFA-producing bacteria, such as Peptococcus ( Wang H. et al, 2023 ), Ruminococcus2 ( Wu et al, 2023 ), Clostridiaceae1 ( Vojinovic et al, 2019 ), and Ruminococcaceae ( D'Amato et al, 2020 ; Zhou et al, 2022 ) were identified to be protective to HSCR, some of which in HSCR was significantly decreased, and were correlated with SCFAs. Animal studies suggested that SCFAs could independently stimulate the enteric neural stem cell phenotype, thereby improving enteric neural disorders ( Fung et al, 2021 ; Tian et al, 2023 ; Wang L. et al, 2023 ). Recent studies revealed that SCFA promoted enterochromaffin cells (ECs) to secrete 5-hydroxytryptamine (5-HT; Atarashi et al, 2013 ; Furusawa et al, 2013 ; Reigstad et al, 2015 ; Yano et al, 2015 ), which is regulated by the calcitonin selective reuptake transporter (SERT) of epithelial cells and plays crucial roles in enteric neuroregeneration and neuroprotection ( Bian et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…This elucidates the crucial role that microbial metabolites play in intestinal health and suggests that boosting the production of beneficial SCFAs may offer a therapeutic strategy for managing constipation. This in-depth analysis enhances our comprehension of how genetic predispositions and gut microbiota configurations impact constipation, significantly broadening our understanding of the microbiome’s role in gastrointestinal health ( Wang L. et al, 2023 ). In addition, previous research has highlighted that butyrate-producing flora can enhance colonic motility and alleviate constipation by inducing the release of serotonin or by stimulating cholinergic pathways through butyrate production.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate maintains intestinal barrier integrity, prevents bacterial endotoxin and inflammatory responses, and reduces interference with intestinal motility[ 11 ]. One study observed that the abundance of Fusobacterium , which is a butyric acid–producing bacteria, is positively correlated with defecation frequency[ 12 ]. Several studies observed the increasing abundance of butyric acid–producing bacteria in the intestine of patients with FC; however, the concentration of butyric acid has yet to be detected[ 9 , 10 ].…”
Section: Disturbed Intestinal Microbiota and Metabolites In Fcmentioning
confidence: 99%